Analisis Implementasi Pemanfaatan Sistem Informasi Manajemen Rumah Sakit (SIMRS) Di RSUD Kardinah Tegal - Dedy Setyawan (Universitas Peradaban, 2015)
Nowadays, the development and advancement of information technology is growing rapidly. System applications in various fields is a must for any institution/company to utilize the information as the basis of administration and data processing. Hospital information system has an important role in clinical and administrative services. Information management in hospitals have started using an electronic-based system (SIMRS), hospitals need a management information system (MIS) to improve the quality of medical services. SIM hospitals (SIMRS) integrated primary function is designed to integrate the hospital into a single integrated system that is stored in the central database. According Jogiyanto (2001: 12) the application is an application, save one thing, the data, the existing problems so it turned into something new shape without losing the basic values of the terms of the data, the problems, the work itself.